2017
DOI: 10.20319/pijss.2017.32.22442259
|View full text |Cite
|
Sign up to set email alerts
|

Social Science Scholars Perception Towards Open Access and Institutional Repositories

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, Zuber 11 strongly supported the findings of Xia through a survey conducted among IRs of universities in the USA. Gunasekhara 12 found that Social Science scholars were not familiar with open-access publishing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Zuber 11 strongly supported the findings of Xia through a survey conducted among IRs of universities in the USA. Gunasekhara 12 found that Social Science scholars were not familiar with open-access publishing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital libraries have become of increasing significance in recent years, developing in functionality and content, and becoming accessible to a wider community of users (Borgman, 2000;Hong et al, 2001;Chowdhury, 2002;Chu, 2003;Andrews & Law, 2004). As in developed countries, university libraries in Sri Lanka have taken steps to digitize their library materials to increase user access to their library collections (Pushpakumara 2007;Hindagolla 2012;Gamage 2013;Balasooriya 2014;Gunasekara, 2017). The university of Peradeniya library network has taken steps to initiate university digital library in 2009.…”
Section: Introductionmentioning
confidence: 99%